The eIF2 Kinase GCN2 Is Essential for the Murine Immune System to Adapt to Amino Acid Deprivation by Asparaginase(2) - Bunpo, Piyawan (American Society for Nutrition, 2010)
Amino acid starvation by asparaginase (ASNase) enhances phosphorylation of eukaryotic initiation factor 2 (eIF2) by general control nonderepressible 2 (GCN2) kinase, leading to reduced global mRNA translation rates. This conserves energy and allows cells time to reprogram stress-related gene expression to alleviate cell injury. This study addressed the importance of GCN2 for the immune system to adapt to amino acid starvation by ASNase. GCN2(+/+) and GCN2(−/−) mice were injected once daily with ASNase or saline for up to 7 d. In both thymus and spleen, activation of amino acid stress response genes to ASNase, such as asparagine synthetase and CAAT enhancer binding protein homologous protein, required GCN2. ASNase reduced food intake and body weight in both genotypes, but spleen and thymus wet weights and total cell numbers in thymus, spleen, bone marrow, and mesenteric lymph nodes were less in GCN2(−/−) mice treated with ASNase (genotype x ASNase, P < 0.05). In the thymus, GCN2(−/−) mice treated with ASNase demonstrated enhanced apoptosis and fewer cells in all subpopulations examined (CD3+, CD4–8-, CD4+8+, CD4+8-, CD4–8+) compared with GCN2(+/+) mice treated with ASNase (genotype x ASNase, P < 0.05). In the spleen, GCN2 deletion magnified ASNase-induced reductions in CD4+ T cells, CD8+ T cells, CD19+ B cells, and CD11b+ leukocytes (genotype x ASNase, P < 0.05). These results indicate that loss of GCN2 enhances immunosuppression by ASNase and that this eIF2 kinase is broadly required for amino acid stress management in the immune system.